Legal Politics of Sea Sand Mining Governance From The Perspective of Blue Economy - Pritasari, Amalia Zulfa; Rachmad Safa’at; Indah Dwi Qurbani (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
The governance of marine sand mining in Indonesia has been controversial since the issuance of Government Regulation No. 26 of 2023 concerning the Management of Sedimentation in the Sea. The discourse on the blue economy in coastal development has been used as the basis for the government to implement governance regulations for coastal and marine areas. The type of research used is legal-normative research employing two approaches: the legal approach and the conceptual approach. The results of this study indicate that the legal policy on the management of marine sand mining does not reflect rules that align with democratic principles. This is evidenced by the fact that the process of making the regulation was not conducted transparently and involved minimal public participation. Based on this, there are two alternative recommendations that can be chosen to address the issue: revising the parts that do not reflect a commitment to the greatest prosperity of the people or implementing a moratorium on policies related to the management of marine sand mining, so that marine sand mining is not reintroduced as it was in 2002. Furthermore, moving forward, the government needs to be more prudent in determining political considerations that are consistently aligned with the principles of the blue economy.